Defining Patient Experience - Jason Wolf (The Beryl Institute, 2014)
In recent years, perceptions of performance and quality of healthcare organizations have begun to move beyond examining the provision of excellent clinical care, alone, and to consider and embrace the patient experience as an important indicator. There is a need to determine the extent to which clear and formal definitions exist, have common overarching themes, and/or have unique, but important constructs that should be considered more widely. In this article, we provide a 14-year synthesis of existing literature and other sources (2000-2014) that have been used to define patient experience. A total of 18 sources (articles or organizational websites) were identified that provided a tangible, explicit definition of patient experience. A narrative synthesis was undertaken to categorize literature (and other sources) according to constructs of the definitions provided. The objectives of the synthesis were to: (1) identify the key elements, constructs, and themes that were commonly and frequently cited in existing definitions of ‘patient experience,’ (2) summarize these findings into what might be considered a common shared definition, and (3) identify important constructs that may be missing from and may enhance existing definition(s). The overarching premise was to identify and promote a working definition of patient experience that is applicable and practical for research, quality improvement efforts, and general clinical practice. Our findings identified several concepts and recommendations to consider with regard to the definition of patient experience. First, the patient experience reflects occurrences and events that happen independently and collectively across the continuum of care. Also, it is important to move beyond results from surveys, for example those that specifically capture concepts such as ‘patient satisfaction,’ because patient experience is more than satisfaction alone. Embedded within patient experience is a focus on individualized care and tailoring of services to meet patient needs and engage them as partners in their care. Next, the patient experience is strongly tied to patients’ expectations and whether they were positively realized (beyond clinical outcomes or health status). Finally, the patient experience is integrally tied to the principles and practice of patient- and family- centered care. As patient experience continues to emerge as an important focus area across healthcare globally, the need for a standard consistent definition becomes even more evident, making it critical to ensure patient experience remains a viable, respected, and highly embraced part of the healthcare conversation. Experience Framework This article is associated with the Culture & Leadership lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Culture%20%26%20Leadership%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D" target="_blank">Access other PXJ articles related to this lens. Access other resources related to this lens.